Protective Role of Vitamin D Receptor in Cerebral Ischemia/Reperfusion Injury In Vitro and In Vivo Model - Jie Dai; Haiyan Huang; Liucheng Wu; Mei Ding; Xiangyang Zhu (Frontiers in Bioscience-Landmark)
Background: Vitamin D receptor (VDR) can prevent myocardial ischemia reperfusion injury (MIRI). Hence, we aimed to illuminate the effect of VDR on cerebral ischemia/reperfusion injury (CIRI). Methods: C57BL/6 mice and SK-N-SH cells were utilized to establish CIRI and cellular oxygen deprivation/reoxygenation (OGD/R) models. Mice were injected with 1 μg/kg Calcitriol or 1 μg/kg Paricalcitol (PC) and adenovirus-mediated VDR overexpression or knockdown plasmids. 2,3,5-triphenyl-tetrazolium chloride (TTC) and Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays were performed to measure the brain infarct volume and the apoptosis of cerebral cells. SK-N-SH cells were treated with 5 mM N-acetyl-L-cysteine (NAC) and transfected with VDR knockdown plasmid. Flow cytometry and Cell Counting Kit-8 (CCK-8) assays were employed to assess the apoptosis and cell viability. Enzyme-Linked Immunosorbent Assay (ELISA), quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) and Western blot were exploited to quantify the levels of reactive species oxygen (ROS), other oxidative stress-related factors, VDR and apoptosis-related factors. Results: The level of VDR in mouse cerebral tissue was elevated by CIRI (p < 0.001). CIRI-induced cerebral infarction (p < 0.001) and the apoptosis of cerebral cells (p < 0.001) in mice were mitigated by the activation of VDR. VDR overexpression abrogated while VDR silencing enhanced CIRI-induced infarction, oxidative stress and apoptosis of cerebral cells (p < 0.05). Furthermore, VDR silencing aggravated the oxidative stress and apoptosis in OGD/R-treated SK-N-SH cells (p < 0.05). NAC, a scavenger of oxidative stress, could reverse the effects of VDR silencing on apoptosis and oxidative stress in OGD/R-treated SK-N-SH cells (p < 0.01). Conclusion: VDR alleviates the oxidative stress to protect against CIRI.